Hepatoprotective Activity Of Chenopodium Album Againist Carbontetra Chloride-Induced Hepatotoxicity In Rats - SUGANTHI. V,; ATHIRA. L. R.NAIR, (International Journal of Pharma and Bio Sciences, 2011)
Many hepatoprotective herbal preparations have been recommended in alternative systems of medicine for the treatment of hepatic disorders. No systematic study has been done on protective efficacy of Chenopodium album to treat hepatic disease. Protective action of Chenopodium album methanol extract was evaluated in animal model of hepatotoxicity induced by carbon tetrachloride (CCl4). The experiments were performed using five groups of animals. The experimental animals were administered with 30 % CCl4 for 14 days and the crude plant extract and the silymarin , a standard drug 25mg/kg/ bwt were fed into the CCl4 treated animals. Liver marker enzymes such as aspartate transaminase (AST), alanine transaminase (ALT), acid phosphatase (ACP), alkaline phosphatase (ALP), lactate dehydrogenase (LDH) were estimated. serum bilirubin and protein levels were evaluated. The present study scientifically validates the traditional use of Chenopodium album for liver disorders.